Industrialisasi di indonesia : beberapa kajian - Thee, Kian Wie. (Jakarta : LP3ES, 1994)
Collection of Articles in Indonesian; originally published in English or Indonesian.
Includes bibliographical references and index.
Mode of access: Internet.
Keywords: Investments, Foreign -- Indonesia; Technology transfer -- Indonesia; Industrialization -- Indonesia; Industries -- Indonesia